Mechanical response of Ti-based bulk metallic glass under plate-impact compression. (August 2015) - Wang, B.P.; Wang, L.; Wang, S.; Fan, Q.B.; Xue, Y.F.; Zhang, H.F.; Fu, H.M.
Abstract: Plate-impact experiments were performed on Ti-based bulk metallic glass (Ti-BMG) using a single stage light gas gun. Both the Hugoniot elastic limit (HEL) and spall strength increased with the increase of impact velocity, and the average HEL was estimated to be 5.34 ± 0.26 GPa. The specimen failed by catastrophic spallation, exhibiting brittle behavior at macroscopic level but ductile behavior at microscopic level. The evolution of spallation was controlled by the initiation and evolution of microcracks. The initiation of microcracks was related to the coalescence of microvoids, tensile stress played a significant role in the nucleation of microvoids during plate-impact. Highlights: Both the HEL and spall strength increased with the increase of impact velocity. Tensile stress induced microvoids formation, resulting in microcracks initiation. Spallation evolution was controlled by initiation and evolution of microcracks.